2009
DOI: 10.1007/s10457-009-9214-1
|View full text |Cite
|
Sign up to set email alerts
|

Can soil plant analysis development values predict chlorophyll and total Fe in hybrid poplar?

Abstract: Iron chlorosis caused by an elevated soil pH remains an important selection criteria in evaluating hybrid Populus trials in northwest New Mexico. Compared to expensive extraction methods or visual ranking scales, the soil plant analysis development (SPAD) chlorophyll meter is a handheld tool that objectively indicates leaf color. SPAD calibration curves pertaining to Fe status in Populus leaves were developed for two clones: NM-6 (Populus nigra 9 Populus maximowiczii) and OP-367 (Populus deltoides 9 Populus ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
(35 reference statements)
3
11
0
5
Order By: Relevance
“…3a). This is consistent with the value reported in a study of a Fe deficient hybrid poplar (P 9 euramericana) (42.5 lg g -1 : Lombard et al 2010). Others studies have reported higher concentrations in other non-nutrient-limited plantations of Populus alba (250 lg g -1 : Madejón et al 2004) and P 9 canadensis (135-486 lg g -1 : Celik et al 2010).…”
Section: Influence Of Forest Nutrition On Tree Growthsupporting
confidence: 90%
“…3a). This is consistent with the value reported in a study of a Fe deficient hybrid poplar (P 9 euramericana) (42.5 lg g -1 : Lombard et al 2010). Others studies have reported higher concentrations in other non-nutrient-limited plantations of Populus alba (250 lg g -1 : Madejón et al 2004) and P 9 canadensis (135-486 lg g -1 : Celik et al 2010).…”
Section: Influence Of Forest Nutrition On Tree Growthsupporting
confidence: 90%
“…1) can also indicate their lower photosynthetic capacity. Highly significant correlations were found between chlorophyll and leaf N and Fe concentrations in the forest (r = 0.86; p \ 0.0001 and r = 0.78; p \ 0.0001, respectively), earlier also reported in other studies (Lombard et al 2010;Weih and Rönnberg-Wästljung 2007). Chlorophyll concentrations in leaves from the grassland were correlated with leaf Fe and Mg content (r = 0.88; p \ 0.0001 and r = 90; p \ 0.0001, respectively) but not with leaf N content (r = 0.27; p [ 0.05).…”
Section: Morphophysiological Characteristics Of Leaves and Fine Rootssupporting
confidence: 84%
“…Chlorophyll concentrations in leaves from the grassland were correlated with leaf Fe and Mg content (r = 0.88; p \ 0.0001 and r = 90; p \ 0.0001, respectively) but not with leaf N content (r = 0.27; p [ 0.05). Mg and Fe play crucial roles in the chlorophyll molecule and photosynthesis, and SPAD readings were closely related to levels of these foliar elements (Klooster et al 2012;Lombard et al 2010). The unreliable relationship between leaf chlorophyll and N concentrations on the grassland may be a consequence of the impact of N Agroforest Syst (2017) 91:307-324 315 concentration and distribution within the leaf and also other factors on SPAD readings (Klooster et al 2012;Lombard et al 2010).…”
Section: Morphophysiological Characteristics Of Leaves and Fine Rootsmentioning
confidence: 99%
“…El análisis de Fe 2+ en la hoja se ha llegado a tomar como un indicador del nivel de abastecimiento de hierro en la planta (Razeto y Valdés, 2006) e investigadores como Köseoğlua y Açikgöza (1995) han llevado a cabo experimentos donde se ha encontrado una alta correlación entre la concentración de clorofila y la de Fe 2+ en la hoja de duraznero (Prunus persica L.), tanto en tejido fresco como en tejido seco. Lombard et al (2010) han llevado a cabo trabajos con apoyo del SPAD 502 para la estimación de Fe en especies forestales como el álamo(Populus ssp.) y en árboles frutales como perales(Pyrus communis L.), en los que se usó este equipo para medir el contenido de clorofila (López-Millán et al, 2001).…”
Section: Introductionunclassified
“…y en árboles frutales como perales(Pyrus communis L.), en los que se usó este equipo para medir el contenido de clorofila (López-Millán et al, 2001). Se tomaron muestras de hojas con diferentes grados de deficiencias de Fe y donde se habían tomado previamente lecturas SPAD (Lombard et al, 2010). Posteriormente, la clorofila se extrajo con acetona al 100 % y en presencia de ascorbato de sodio dado que se supone, existe correlación entre el contenido de Fe y de clorofila.…”
Section: Introductionunclassified